REM sleep behavior disorder, as assessed by questionnaire, in G2019S LRRK2 mutation PD and carriers. Issue 13 (14th September 2015) - Saunders‐Pullman, Rachel; Alcalay, Roy N.; Mirelman, Anat; Wang, Cuiling; Luciano, Marta San; Ortega, Roberto A.; Glickman, Amanda; Raymond, Deborah; Mejia‐Santana, Helen; Doan, Nancy; Johannes, Brooke; Yasinovsky, Kira; et al.
Abstract: Background: Rapid eye movement sleep behavior disorder occurs with idiopathic Parkinson's disease (PD) and often precedes PD. Its frequency in LRRK2 ‐PD and utility as a preclinical marker has not been established. Methods: One hundred forty‐four idiopathic PD, 142 LRRK2 G2019S mutation PD, 117 non‐manifesting carriers, 93 related noncarriers, and 40 healthy controls completed the Rapid eye movement sleep Behavior Disorder Screening Questionnaire. Results: Cut scores were met by 30.6% idiopathic PD, 19.7% LRRK2 ‐PD, 6% nonmanifesting carriers, 20.4% related noncarriers, and 15% controls. The likelihood of abnormal scores was decreased in LRRK2 ‐PD versus idiopathic PD (odds ratio = 0.55, P = 0.03), nonmanifesting carriers versus related noncarriers (OR = 0.25, P < 0.01), and PD of less than 3 years' duration, 1 of 19 LRRK2 ‐PD versus 14 of 41 idiopathic PD ( P < 0.05). Conclusions: A lower frequency of abnormal questionnaire scores is seen in LRRK2 ‐PD, especially in early LRRK2 ‐PD, and in nonmanifesting carriers. Therefore, the Rapid eye movement sleep Behavior Disorder Questionnaire is unlikely to serve as a preclinical marker for phenoconversion to PD. © 2015 International Parkinson and Movement Disorder Society